1978
DOI: 10.1159/000114972
|View full text |Cite
|
Sign up to set email alerts
|

Charcot-Marie-Tooth Disease with Sex-Linked Inheritance, Linkage Studies and Abnormal Serum Alkaline Phosphatase Levels

Abstract: A family with Charcot-Marie-Tooth disease (CMT) is described. An irregular dominant sex-linked inheritance is observed. No linkage relationship between the Xg(a) blood group locus and the CMT locus was established. Abnormal values of the serum alkaline phosphatase level were found in affected and unaffected members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the past, a few reports on the regional localisation of the CMTZ gene have appeared. Absence of linkage to the Xg blood group was demonstrated in a study of a family suffering from X-linked partially dominant CMT (de Weerdt et al 1976, de Weerdt 1978. It is also known that the locus for colour blindness is unlinked to the CMT2 locus (Iselius & Grimby 1982).…”
mentioning
confidence: 98%
“…In the past, a few reports on the regional localisation of the CMTZ gene have appeared. Absence of linkage to the Xg blood group was demonstrated in a study of a family suffering from X-linked partially dominant CMT (de Weerdt et al 1976, de Weerdt 1978. It is also known that the locus for colour blindness is unlinked to the CMT2 locus (Iselius & Grimby 1982).…”
mentioning
confidence: 98%
“…In 1978, de Weerdt [6] demonstrated linkage of CMTX to the proximal long arm of the X chromosome, and, in 1993, Bergoffen et al [7] demonstrated seven mutations in the Cx32 gene in eight CMTX families. Thus far, over 160 different mutations have been reported in the Cx32 gene in CMTX families [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…In CMTX kindreds. there is no male-to-male transmission, and males are affected before their twenties (Allan, 1939;Erwin, 1944;Woratz, 1964;de Weerdt, 1978;Fryns and Van den Berghe, 1980;Phillips et aL, 1985;Rozear et aL, 1987;Hahn et aL, 1990;Skre, 1974). In some studies, obligate female carriers were not reported to be affected, hence these kindreds were considered to have X-linked recessive CMT.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 99%